Projeto, montagem e testes de um amplificador de áudio de 5.1 canais - Visintin, Rafael Marchiori (Universidade Federal de São Carlos, 2013)
In this paper, was developed the project of an audio amplifier of 5.1 channels in order to use as a home theater. The amplifiers are all constructed in printed circuit boards, using audio transistors. Initially, was established a topology, and then, was studied the effects of the resistors of each stage of the circuit over the performance of the circuit. The measurements were made using the equipment from Nuleen laboratory.
Design, assembly and tests of a 5.1 channel audio amplifier
Keywords: Áudio; Amplificadores transistorizados; Amplificadores 5.1 canais; Home Theater; ENGENHARIAS::ENGENHARIA ELETRICA